Factors that influence the prevention of cervical cancer in the quilombo - Kamila Santana Jacintho; Kariane Omena Ramos Cavalcante; Jovania Marques de Oliveira e Silva; Amuzza Aylla Pereira dos Santos (Universidad de Alicante, 2018)
Objective: To identify factors that influence the prevention of cervical cancer in quilombola women. Method: It is an ethnographic study, the study population was composed of women attending the Basic Health Unit of this community. For the data collection were used: form, observation and health education workshops. The analysis consisted of reading and re-reading the interviews, systematizing them, classifying the units of significance and then categorizing them. Results: The non-adherence of the women was higher in black, elderly and low schooling. The shame and fear of exposure were other points, which hinder the performance of the preventive examination. Conclusion: It is important to emphasize that health education is a factor that can contribute to these women know more about the preventive exam and can acquire information, clarify doubts and prevent cervical cancer.